Oncological impact of neoadjuvant hormonal therapy on permanent iodine‐125 seed brachytherapy in patients with low‐ and intermediate‐risk prostate cancer. (12th April 2018) - Takamoto, Atsushi; Tanimoto, Ryuta; Bekku, Kensuke; Araki, Motoo; Sadahira, Takuya; Wada, Koichiro; Ebara, Shin; Katayama, Norihisa; Yanai, Hiroyuki; Nasu, Yasutomo
Abstract : Objectives: To determine whether neoadjuvant hormonal therapy improves oncological outcomes of patients with localized prostate cancer treated with permanent brachytherapy. Methods: Between January 2004 and November 2014, 564 patients underwent transperineal ultrasonography‐guided permanent iodine‐125 seed brachytherapy. We retrospectively analyzed low‐ or intermediate‐risk prostate cancer based on the National Comprehensive Cancer Network guidelines. The clinical variables were evaluated for influence on biochemical recurrence‐free survival, progression‐free survival, cancer‐specific survival and overall survival. Results: A total of 484 patients with low‐risk (259 patients) or intermediate‐risk disease (225 patients) were evaluated. Of these, 188 received neoadjuvant hormonal therapy. With a median follow up of 71 months, the 5‐year actuarial biochemical recurrence‐free survival rates of patients who did and did not receive neoadjuvant hormonal therapy were 92.9% and 93.6%, respectively ( P = 0.2843). When patients were stratified by risk group, neoadjuvant hormonal therapy did not improve biochemical recurrence‐free survival outcomes in low‐ ( P = 0.8949) or intermediate‐risk ( P = 0.1989) patients. The duration or type of hormonal therapy was not significant in predicting biochemical recurrence. In a multivariate analysis, Gleason score, pretreatment prostate‐specific antigen, clinical T stage, and prostate dosimetry, primary Gleason score and positive core rate were significant predictive factors of biochemical recurrence‐free survival, whereas neoadjuvant hormonal therapy was insignificant. Furthermore, neoadjuvant hormonal therapy did not significantly influence progression‐free survival, cancer‐specific survival or overall survival. Conclusions: In patients with low‐ or intermediate‐risk disease treated with permanent prostate brachytherapy, neoadjuvant hormonal therapy does not improve oncological outcomes. Its use should be restricted to patients who require prostate volume reduction.